Ripper [compact disc, unabridged] : a novel - Allende, Isabel (HarperAudio, 2014)
"A fast-paced mystery involving a brilliant teenage sleuth who must unmask a serial killer in San Francisco through Ripper, the online mystery game she plays with her beloved grandfather and friends around the world"--